Information technology. International standardized profiles FVT2nn. Virtual terminal basic class. Register of control object type definitions. FVT231. Forms FEPCO (Field Entry Pilot Control Object) No.1 Part 10, (15th March 1995) - British Standards Institution,
No abstract available